Documentation of The Saperra Manre Through The Documentary Film - Suparman, Suparman; Madeamin, Sehe; Beta, Pancana (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2018)
This study aims to document the value of manre saperra in terms of preserving and restoring noble values ​​in regional culture as well as strengthening the character of the nation's children in facing globalization.This research will be conducted in Luwu Utara District. The data source of this research is the ritual procession of manre saperra of North Luwu society. The existence of this ritual manre saperra has begun to be abandoned and is not known by most of the Luwu community including the young generation. Therefore, in order to introduce the values ​​of nobility in this manner saperra ritual to the Tana Luwu community in particular and to the general public in general, the documentary film becomes a container of documentation and publication of manre saperra ritual. The documentary aims to document and visualize the audio visual process of manre saperra which contains many noble values ​​in its implementation to the Tana Luwu community and to the general public at large, as well as creating a documentary film that is able to convey the message contained in order to obtain a positive response from all parties. This documentary was made with the stages of data collection in the form of research observation, interview, literature study, and film compilation. The result of this research is by making a documentary about manre saperra procession, the society is expected to be more know and recognize and practice the values ​​contained in manre saperra ritual so that this documentary film can be used as media of information and learning media for younger genres in knowing local culture. Documentation of the prosei manre saperra through documentary film as a form keeps the authenticity of the values ​​formed in the custom procession.